Male neonatal circumcision - Di Pietro, Maria Luisa; Cicerone, Marina (Medicina e Morale, 2000)
The term "circumcision" points out the total or partial removal of the prepuce in the male, a practice present since the antiquity and performed today still in different geographical areas for religious and cultural motivations. After a brief historical excursus, the Authors analyse the reasons for the masculine neonatal circumcision (preventive, therapeutic and ritual) and the possible related complications (physical and psychological), with the purpose to have objective data to appraise the utility and its effectiveness at the clinical level. It deals with a not easy evaluation, so much that the generally advanced proposal is to leave the choice to the parents whether to circumcise or not their child. Are the parents able to take the correct decision? Are they able to express an informed consent? And does the informed consent from the parents guarantee the defence of the good interest of their child? Which adhesion of their child would have been to the proposal of circumcision if he had been able to intend and to want? Another aspect is that of the application of ritual circumcision: is made at National Healthcare Service expense this intervention? The matter, taking in examination from the National Committee for Bioethics (Italy), is already analysed from the point of view of the recognition of these forms of worship and about the validity of the preventive circumcision.